2001
DOI: 10.1161/01.hyp.38.2.267
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Biological Actions of Coronary Endothelial Nitric Oxide During Progression of Cardiac Hypertrophy

Abstract: Abstract-Coronary endothelial NO synthase expression and NO bioactivity were investigated at sequential stages during the progression of left ventricular hypertrophy. Male guinea pigs underwent abdominal aortic banding or sham operation. Left ventricular contractile function was quantified in isolated ejecting hearts. Coronary endothelial and vasodilator function were assessed in isolated isovolumic hearts in response to boluses of bradykinin (0.001 to 10 mol/L), substance P (0.01 to 100 mol/L), diethylamine N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 46 publications
1
13
0
5
Order By: Relevance
“…As reported previously, 13 LV/body weight ratio was significantly higher by 3 weeks after surgery in the banded group compared with the sham group. Lung/body weight ratio was increased in the banded group by 10 weeks after surgery ( Figure 1A and 1B).…”
Section: Nadph-dependent Ros Generation During Progression Of Lvhsupporting
confidence: 87%
See 2 more Smart Citations
“…As reported previously, 13 LV/body weight ratio was significantly higher by 3 weeks after surgery in the banded group compared with the sham group. Lung/body weight ratio was increased in the banded group by 10 weeks after surgery ( Figure 1A and 1B).…”
Section: Nadph-dependent Ros Generation During Progression Of Lvhsupporting
confidence: 87%
“…Male Dunkin-Hartley guinea pigs (200 to 250 g; Harlan UK Ltd, Bicestor, UK) underwent suprarenal abdominal aortic banding or sham banding. 13 Aortic banding in guinea pigs is a well-established model of pressure-overload LVH that has been preferred over small rodent models in several studies because guinea pig LV more closely resembles human myocardium with respect to myosin heavy-chain isoform expression and electrophysiological characteristics. In this model, compensated LVH is present from 2 weeks after surgery followed by a transition phase from 4 to 6 weeks and then overt LV decompensation at 8 to 10 weeks.…”
Section: Experimental Hypertrophymentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Although reactive oxygen species might be generated by diverse cellular mechanisms, abnormal activation and expression of myocardial NAD(P)H-oxidase have been suggested to be the main source of reactive oxygen species in the hypertrophic and failing myocardium. 3,5,6 Experimental data are accumulating, suggesting that the combination of superoxide (O 2 Ϫ ) and nitric oxide (NO), releasing peroxynitrite, may also contribute to the pathogenesis of myocardial dysfunction and damage triggered by a variety of stress, including ischemia, cytokines, and sepsis. 7 These detrimental effects are thought to be consequent of larger tissue concentrations of NO or O 2 Ϫ .…”
mentioning
confidence: 99%
“…16 In this sense, previous studies have reported a selective decrease of eNOS cardiac protein in different models of cardiac hypertrophy. 17,18 The recent generation of transgenic mice models with a lack or an overexpression of eNOS protein has also demonstrated the importance of this enzyme in the process of cardiac remodeling. 19,20 More recently, Wenzel et al 21 have demonstrated that inhibition of eNOS-derived NO induces hypertrophy development in adult ventricular cardiomyocytes.…”
Section: Ruiz-hurtado Et Al La419 Prevents Maladaptative Cardiac Remomentioning
confidence: 99%